2017
DOI: 10.3126/jnhrc.v15i2.18197
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Life Support Equipment and its Utilization by Ambulance Drivers

Abstract: Background: An effective ambulance is a vital requirement for providing an emergency medical service. Wellequipped ambulances with trained paramedics can save many lives during the golden hours of trauma care. The objective was to document the availability and utilization of basic life support equipment in the ambulances and to assess knowledge on first aid among the drivers. Methods:Descriptive design was used. Total of 109 ambulances linked to B.P. Koirala Institute of Health Sciences were enrolled using pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 1 publication
1
5
2
Order By: Relevance
“…Contrary to other studies from Nepal (13,18), this study found that most 293 (95.1%) ambulances drivers were trained in basic first aid. Very few 9 (2.9%) ambulances were reported to have trained paramedics or Emergency Medical Technicians (EMTs).…”
Section: Ambulance Facilitycontrasting
confidence: 99%
“…Contrary to other studies from Nepal (13,18), this study found that most 293 (95.1%) ambulances drivers were trained in basic first aid. Very few 9 (2.9%) ambulances were reported to have trained paramedics or Emergency Medical Technicians (EMTs).…”
Section: Ambulance Facilitycontrasting
confidence: 99%
“…One of the key areas that marked most agreed group-perceived satisfaction was patient-handling techniques of the ambulance crew. Skills of critical patient handling need to have sound knowledge of different emergencies, awareness of complications [10], and the ability to handle emergency equipment used in the provision of on-site critical care [11]. The result of the study confirms that use of appropriate equipment, specifically, oxygen, face mask, cervical collars, spinal boards, and splints, and techniques, particularly, cervical stabilization and log rolling techniques, were within the expected degree of the A&E staff.…”
Section: Discussionmentioning
confidence: 56%
“…There was no AED in any ambulances in their study. 11 In present study, majority of the ambulances were equipped with basic equipment used for first aid only like dressing, pain management, and so on. Due to the lack of trained staff, these ambulances only serve the purpose of transportation of the victim to the health centers.…”
Section: Discussionmentioning
confidence: 93%
“…A study conducted by Acharya et al, highlighted that 77% participants were having a secondary/10 + 2 level of education. 11 According to Hansda et al, around 60% had a 10 + 2 or above level of education. 20 In the present study, only 9.00% had training course on CPR and according to other study, 24% staff had done CPR training course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation